Identification of a Prognostic Signature Associated With DNA Repair Genes in Ovarian Cancer - Sun, Hengzi; Cao, Dongyan; Ma, Xiangwen; Yang, Jiaxin; Peng, Peng; Yu, Mei; Zhou, Huimei; Zhang, Ying; Li, Lei; Huo, Xiao; Shen, Keng (Frontiers in Genetics, 2019)
Introduction: Ovarian cancer is a highly malignant cancer with a poor prognosis. At present, there is no accurate strategy for predicting the prognosis of ovarian cancer. A prognosis prediction signature associated with DNA repair genes in ovarian cancer was explored in this study. Methods: Gene expression profiles of ovarian cancer were downloaded from the GEO, UCSC and TCGA databases. Cluster analysis, univariate analysis and stepwise regression were used to identify DNA repair genes as potential targets and a prognostic signature for ovarian cancer survival prediction. The top genes were evaluated by immunohistochemical staining of ovarian cancer tissues, and external data were used to assess the signature. Results: A total of 28 DNA repair genes were identified as being significantly associated with overall survival (OS) among patients with ovarian cancer. The results showed that high expression of XPC and RECQL and low expression of DMC1 were associated with poor prognosis in ovarian cancer patients. The prognostic signature combining 14 DNA repair genes was able to separate ovarian cancer samples associated with different OS times and showed robust performance for predicting survival (Training set: p ˂ 0.0001, AUC = 0.759; Testing set: p ˂ 0.0001, AUC = 0.76). Conclusion: Our study identified 28 DNA repair genes related to the prognosis of ovarian cancer. Using some of these potential biomarkers, we constructed a prognostic signature to effectively stratify ovarian cancer patients with different OS rates, which may also serve as a potential therapeutic target in ovarian cancer.